In-vitro antimicrobial activity of Fosfomycin Tromethamine against Urinary Extended Spectrum Beta Lactamase producing Escherichia coli and Klebsiella Pneumoniae - Khan, Mumtaz Ahmad (International Journal of Pathology, 2019)
Background: Escherichia coli and Klebsiella pneumonia are the most common infecting organisms in patients with uncomplicated Urinary tract infections. Resistance against most of the commonly used antibiotics is increasing. Fosfomycin tromethamine is still effective in UTIs especially in Extended spectrum beta lactamase (ESBL) producing bacteria. Objective: To determine in vitro antimicrobial activity of fosfomycin tromethamine in extended spectrum beta lactamase producing E coli and Klebsiella pneumoniae causing urinary tract infections. Methods: This was a descriptive cross-sectional study carried out at Abbas Institute of Medical Sciences, AIMS, Muzaffarabad from January 2017 to December 2017. Urine specimens from suspected cases of UTI were inoculated on cysteine lactose electrolyte deficient (CLED) agar and incubated aerobically at 35oC ± 2 for 16-18 hours. After identification of Gram-negative rods; the isolates were screened for ESBL with cefotaxime 30 μg disc by Kirby-Bauer disc diffusion technique. The isolates with cefotaxime zone diameter equal to or less than 27 mm were further confirmed for ESBL by phenotypic confirmatory test applying cefotaxime and clavulanic acid 30/10 μg combination disc (double disc synergy). The inoculums of bacterial suspensions were plated on Mueller-Hinton agar with subsequent application of Fosfomycin tromethamine disc 200 μg. Plates were incubated overnight aerobically. Subsequently, resulting zone diameters were interpreted according to Clinical &Laboratory Standards Institute guidelines. Results: Out of 84 ESBL producing Gram negative isolates, 81% (n=68) were identified as E coli and 19% (n= 16) as Klebsiella peumoniae. The age of the patients in ESBL producing urinary isolates ranged from 1 to 80 years, with larger numbers around 60 years of age. According to the study results, 82% (n=79) of E. coli and 75% (n =18) of Klebsiella peumoniae were susceptible to Fosfomycin tromethamine. Conclusion: Fosfomycin has shown good sensitivity against ESBL producing E coli and Klebsiella pneumoniae emphasizing its role to be used in empirical therapy for simple lower urinary tract infections caused by these uropathogens